The Effectiveness of Herbal Sanitary Pads in Reducing the Incidence and Severity of Fluor Albus Among Women - Ellora, Yuneta; Putri, Elyanisa (International Journal on ObGyn and Health Sciences, 2024)
This study investigates the effectiveness of herbal sanitary pads in reducing the incidence and severity of Fluor Albus, a common condition characterized by abnormal vaginal discharge. Utilizing a randomized controlled trial design, 200 women aged 18 to 45 experiencing symptoms of Fluor Albus were recruited and divided into two groups: one using herbal sanitary pads infused with natural antimicrobial herbs and the other using conventional pads. Over three menstrual cycles, participants documented changes in discharge frequency, severity, and overall comfort. Results indicated a significant reduction in both the frequency and severity of Fluor Albus symptoms among users of herbal pads, with 65% reporting improvement compared to 35% in the control group (p < 0.01). Additionally, participants using herbal pads reported enhanced comfort and satisfaction, with 80% expressing a preference for continued use beyond the study period. These findings suggest that herbal sanitary pads may serve as an effective alternative for managing Fluor Albus, promoting better vaginal health and empowering women to make informed choices regarding their menstrual hygiene.